Performance Simulation of HF-VHF Mobile Radio Systems in a Tactical Vehicle - Sathyamurthy, S.; Sundaresh, S. (Defence Science Journal, 2008)
A simulation process evolved for evaluating the performance of HF-VHF multi-radio set configuration ina tactical command vehicle is discussed. Algorithms and performance models used in the simulation process arebriefly described. Simulation process is for a specific application in a defined area of deployment under knownoperating situations. Performance simulation also includes an interference simulation model corresponding to thesystem model so that a real world situation is analysed to the practicable extent. Wherever statistical data ormanufacturer's design data is not available, suitable default values are assumed for applicable, battlefield scenarioquoted in the literature. This simulation tool can be extended to many applications (with modification to RFpower of transmitters, receiver sensitivity, frequency separation, distance separation, channel spacing, frequencyrange, communication range, etc. of tactical vehicles operating in combinations of HF-VHF-UHF regions). Defence Science Journal, 2008, 58(6), pp.762-767, DOI:http://dx.doi.org/10.14429/dsj.58.1704